An investigation on the prevalence and drug susceptibility of Salmonella enterica and Shigella dysenteria pathogens in Beitbridge town - Madziwa, Tapiwa O. (Midlands State University, 2019)
Salmonella enterica and Shigella dysenteria are different groups of Gram-negative bacteria. Salmonella infection affects the small and large intestine (enterocolitis) whereas Shigella infection affects the colon (colitis). Diarrhea, abdominal pain and fever are the main symptoms in both diseases. The study was conducted among Beitbridge residents who visited Beitbridge District Hospital suffering from diarrhea in the months December 2017 and January 2018. The aim of the study was to determine the prevalence of Salmonella enterica and Shigella dysenteria in Beitbridge residents. Determining the most effective antibiotic in the treatment of the patients with Salmonella enterica and Shigella dysenteria was also of great concern. After culturing 154 stool samples, twenty-seven (7.1%) were found to be infected with Salmonella enterica and Shigella dysenteria or both. Children below the age of 12 years (8.4%) and female (9.7%) were mostly infected with Salmonella enterica and Shigella dysenteria for they are the most active groups in the society. Salmonella enterica and Shigella dysenteria were resistant to at least one of the six antibiotics used. The most effective antibiotics were ceftriaxone and ciproflacillin (were both susceptible to 100% of Salmonella enterica and Shigella dysenteria) and this showed that these two antibiotics are the most effective drugs for treatment of Salmonella enterica and Shigella dysenteria. It was concluded that Salmonella enterica and Shigella dysenteria prevalence is high in the high-density area (14.9%) than in the low-density area (2.6%) of Beitbridge town. Salmonella and Shigella infections are reported urgently after isolation according to Ministry of Health. Measures by the local authority and Ministry of Health should be put in place to reduce prevalence of the two infectious bacteria.